Composition as pattern, as structure, as expression. (Mount Kisco, N.Y. Center for Humanities, 1986)
Describes composition in art as serving purposes of decoration, structure, and expression, and discusses how the painter organizes the surface of his painting to meet these ends. Considers linear rhythm and flat pattern in two-dimensional paintings.
Keywords: Composition (Art).; Art studies; Humanities